Estudo da Nucleação Supercondutora em Estruturas Híbridas Supercondutor/Ferromagnético - Martins, Thiago Bispo (2015)
The relation between magnetism and superconductivity always has been a challenge for condensed matter physics, and at the same time, essential for the understanding of the superconductivity. In principle, the Meissner effect assumes that both phenomena are excluding. However, recent advances in thin films technology have allowed the development of hybrid systems where superconducting and magnetic systems coexist. Furthermore, the physical properties of both systems are mutually modifies. The principal objective of this work is to perform a study, from theoretical point of view, of bilayers created by magnetic and superconducting layers. In essence, it is studied how the magnetic structure of a ferromagnetic system affects the superconducting order parameter inside the superconductor. The dependence of the critical temperature with the magnetic field is studied using the Ginzburg - Landau theory. Also is studied how the superconducting order parameter localizes in superconducting samples which have dimensions of the same order as, for example, the superconducting coherence length. Bilayers where the magnetic layer structure introduces a homogeneous uniaxial magnetization were studied. Also it was considered the possible influence of magnetic domains which are presented in the magnetic systems. The results show that depending of the geometry of the superconductor system the superconducting nucleation will arise at the edges of the films, or inside the domain wall between magnetics domains. The results reproduce experimental results found in the literature and provide new insights about the nucleation of the superconducting order parameter in mesoscopics systems.